Pemilihan Program Studi Menggunakan Algoritma FP-Growth dan J48 - Norhikmah; Rumini (Jurnal ICT: Information Communication & Technology, 2022)
The study program is an absolute thing and must be chosen by prospective new students when registering to become a student, the lack of knowledge of the courses offered by the campus becomes a difficulty in determining study programs that match their interests. The first research method of analyzing data uses the association rule to get the relationship of study programs with other study programs, and subsequently classifies the study program using decision tree j48, and is followed by examiners using confusion matrux. The results of this study are to use the association rule Fp-Growth method obtained 10 best rules, namely for the first rule D3 Informatics with International Relations. Of the 10 rules obtained as a reference or basis for determining classes on the j48 algorithm, from the results of the 10 rules, analyzed according to the rules applied in Amikom, then obtained into 11 classes where the rules are based on the origin of natural science or social studies schools. By using the j48 algorithm, 99.8% accuracy is obtained with the highest hierarchy in the decision tree, namely the D3 Informatics study program and for the origin school, namely IPS high school